The Relationship Between School Bag Load And The Degree Of Scoliosis Spinal Curve In Children Aged 8-12 Years - Abdul Azis, Reza Ghani; Faris Naufal, Adnan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Introduction: Carrying a bag that is too heavy, especially if it exceeds 10% of a child's body weight, is one of the risk factors that can cause postural disorders. This condition can have an impact on changes in the degree of spinal curvature, especially in the context of scoliosis. Objective: This study aims to examine the relationship between bag weight and the degree of scoliosis spinal curvature in children. Method: This study used a quantitative approach with a cross-sectional observational design. The determination of the number of samples was based on the Slovin formula. The design used was a one-group design with an additional analytical approach to evaluate the effects caused. Data were collected by measuring the weight of the bag using a digital scale and measuring the curvature of the spine using a scoliometer. Results: The results of the Kolmogorov-Smirnov test showed that the data did not follow a normal distribution. The Spearman correlation test indicated a relationship between bag weight and the degree of spinal curvature, although the relationship was weak. In addition, the Wilcoxon test showed a significant difference between the two measurement methods used. Conclusion: There is a significant relationship between bag weight and spinal curvature in children aged 8 to 12 years.